Knowledge and Practice of Umbilical Cord Clamping among Maternity Care Providers - Girija Madhavanprabhakaran; Allende Wittmann; Gowri Vaidyanathan; Tamima Aldughaishi; Deepa Shaji Thomas (Mashhad University of Medical Sciences, 2018)
Background & aim: Based on the current scientific evidence, delayed cord clamping (DCC) elevates early hemoglobin concentrations and iron stores in the neonate. However, the persistent practice of early cord clamping (ECC) is still a routine care. The aim of the present study was to investigate the umbilical cord clamping practices of maternity care providers in Oman. Methods: This cross-sectional study was conducted on 175 maternity care providers who were registered members of the Oman Society of Obstetricians and Gynecologists and participated voluntarily in the study. The data were collected using a modified version of an online survey in form of a questionnaire developed by Stoll and Hutton (2012). The data were analyzed using descriptive statistics. Results: According to the results, 61% and 31% of the participants were obstetricians and midwifes, respectively, with more than 10 years of experience. The findings indicated that the timing of cord clamping varied among the participants. 87.4-89.6% of the care providers considered ECC timing to be within 1 min of birth, and 70-72.6% of them clamped umbilical cord within 1 min for both normal term and preterm newborns. The most frequently listed benefits of DCC were the physiologic transitioning of the newborn, enhancement of neonatal iron stores, reduced risk of neonatal anemia, and decreased need for transfusions. 45.7% of the participants considered polycythemia and jaundice as the highest associated risks of DCC. Only 11% of the participants reported that they use hospital policy as a reference guide on decision making regarding the timing of cord clamping. Conclusion: Although the majority of the maternity care providers are aware of the new guidelines regarding the timing of cord clamping, they still follow ECC practice. The high prevalence of ECC highlighted the demand for the implementation of a nation- and hospital-wide policy.